Pengaruh Program Airport Educational Tour “Discover YIA” Bandar Udara International Yogyakarta Terhadap Ketertarikan Masyarakat Tentang Kebandarudaraan - Tri Febriantini; Nur Makkie Perdana Kusuma (Jurnal Universal Technic, 2023)
The Discover YIA program is a commitment of PT Angkasa Pura I (Persero) in providing services and comfort to airport service users, as well as an effort to support information disclosure and education processes regarding local cultural wisdom and Yogyakarta icons at Yogyakarta International Airport. This study aims to determine the influence of the "Discover YIA" Educational Tour Airport Tour Program to influence public interest in airports and to find out how much influence the "Discover YIA" Educational Tour Airport Tour Program has on public interest in airports. This study used quantitative research methods with data collection techniques using questionnaire distribution to 96 people who had participated in the YIA discover program. Data analysis techniques consist of research instruments, namely validity tests and reliability tests and hypothesis tests consisting of simple linear analysis tests, t tests, and determination coefficients. The result of this study is the Airport Tourism Program Educational Tour "Discover YIA" Yogyakarta International Airport has a positive and significant effect on public interest in airports with a significant number of 0.004 and the number of r count > r table or 2.961> 1.985. The influence of the Yogyakarta International Airport Educational Tour "Discover YIA" Airport Tourism Program on public interest about the airport is 50.9%.